2004
DOI: 10.1016/j.str.2004.04.013
|View full text |Cite
|
Sign up to set email alerts
|

1.2 Å Crystal Structure of the Serine Carboxyl Proteinase Pro-Kumamolisin

Abstract: Kumamolisin, an extracellular proteinase derived from an acido/thermophilic Bacillus, belongs to the sedolisin family of endopeptidases characterized by a subtilisin-like fold and a Ser-Glu-Asp catalytic triad. In kumamolisin, the Asp82 carboxylate hydrogen bonds to Glu32-Trp129, which might act as a proton sink stabilizing the catalytic residues. The 1.2/1.3 A crystal structures of the Glu32-->Ala and Trp129-->Ala mutants show that both mutations affect the active-site conformation, causing a 95% activity dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
76
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(83 citation statements)
references
References 43 publications
7
76
0
Order By: Relevance
“…Given that mixed inhibition can lead to an uncompetitive kinetics (32), it may be difficult to unequivocally distinguish these two modes of inhibition (33). The high resolution structure of the intact prokumamolisin, as the first prosedolisin, has been resolved recently (38), and it has been shown that the prosegment exhibits a half-␤ sandwich core docking to the catalytic domain, similarly to the equivalent subtilases and PCs. Given the overall structural similarity of sedolisins (5), a similar arrangement of the TPP I prosegment and catalytic domain of TPP I might be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Given that mixed inhibition can lead to an uncompetitive kinetics (32), it may be difficult to unequivocally distinguish these two modes of inhibition (33). The high resolution structure of the intact prokumamolisin, as the first prosedolisin, has been resolved recently (38), and it has been shown that the prosegment exhibits a half-␤ sandwich core docking to the catalytic domain, similarly to the equivalent subtilases and PCs. Given the overall structural similarity of sedolisins (5), a similar arrangement of the TPP I prosegment and catalytic domain of TPP I might be expected.…”
Section: Discussionmentioning
confidence: 99%
“…The positioning of Pro8 is critical as it points away from the body of the protein so moving the scissile peptide bond out of reach of the catalytic serine. This is in contrast to the mode of binding of the classical prodomains from ESPs (26)(27)(28) and the subtilisin-like proteins kumamolisin (29,30) and fervidolysin (31) over the active site, which retain the target peptide bond in a position to allow autocatalytic processing. Interactions between subtilisins and classical proteinacous inhibitors (32,33) such as CI2 (34) are normally restricted to the active site and substrate binding region whereas the N-terminal extension of ISP forms distinct interactions with regions of the protein beyond the substrate binding pocket.…”
Section: Discussionmentioning
confidence: 89%
“…Comparison of the structure of proISP with that of NΔ 18 -ISP S250A determined here provides an explanation and reveals that the N-terminal extension regulates protease activity via an additional mechanism: disruption of the catalytic triad and S1 binding pocket. Leu6 and Tyr9 within the N-terminal extension point toward the loop carrying the catalytic serine mutation resulting in displacement of the main-chain atoms of the loop containing Ala250 by ∼1 Å compared to other subtilisins, including those with the active site serine residue mutated to alanine (26,30). This results in Ala250 being displaced by ∼1.6 Å from the position required for the formation of a catalytic triad.…”
Section: Discussionmentioning
confidence: 99%
“…As pointed out by Guhaniyogi et al (28), there is a good agreement between the structures of the glycosylated TPP1 precursor and the Endo H-deglycosylated one (PDB ID 3EDY). Furthermore, the crystal structure of pro-kumamolisin, the most homologous bacterial member of the sedolisin family, showed that the connecting linker runs through the entire active site cleft (17). Superposition of pro-kumamolisin with the active kumamolisin revealed that the catalytic domain of the proenzyme exhibits an almost identical structure and is already properly prefolded within the proenzyme (18).…”
Section: Discussionmentioning
confidence: 99%
“…The TPP1 precursor shares only 18.7% of its amino acid sequence with pro-kumamolisin that is currently the only reported structure of a full-length S53 peptidase. However, superposition of the reported structure of pro-kuma- molisin (17) with this full-length TPP1 structure reveals a 1.64 Å root mean square deviation of the 376 matching C-␣ atoms (supplemental Fig. S2).…”
Section: Homology Of Tpp1 To Members Of the Sedolisin Family Of Serinementioning
confidence: 99%